Competency Development Salt Farmers Skills in Pademawu Sub-District Pamekasan Regency - Sukron Ma'mun; Abdurahman Abdurahman; Abubakar Basyarahil (International Journal of Entrepreneurship and Sustainability Studies, 2021)
Many salt-farmers in Pademawu lived in the middle to lower economic class because they still produced bad raw-salt. This study aimed to arrange a new model of developing salt-farmers skill to produce a high amount of salt in better quality. Qualitative method was used in this study. The data presented were the result of interview and observation. The researher acted as a research intrument that went directly to the fielt to obtain accurate data. The data analysis technique used was domain analysis, which sought to analyze general descriptions of research object at surface level but relatively intact about the object of research. The result analysis of this study was targetted to obtain complete description of the object without mentioned detail elements of the object research. This research only discusses the development of salt farmer skills competency. This research was expected to give valuable contribution of model of developing salt-farmers skills.